Law Enforcement Against Perpetrators of Domestic Violence in the Tual Regional Police Jurisdiction: A Research Study at the Tual Regional Police - Sihombing, Yossri Mantaw; Sumarno; Muhammad Arif Sahlepi (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Law enforcement against perpetrators of physical violence in the household is an important part of protecting victims, especially women. This study aims to analyze the factors causing physical violence in the household, the efforts to overcome it carried out by the Tual Police, and the forms of law enforcement against perpetrators. This study uses a descriptive analytical method with a normative and sociological juridical approach. Data were obtained through interviews, observations, documentation, and literature studies. The results of the study indicate that the factors causing Domestic Violence in the jurisdiction of the Tual Police include alcohol abuse, economic problems, infidelity, and low legal education. The Tual Police have made efforts to overcome this through preventive and repressive measures, but the implementation of law enforcement still faces obstacles such as withdrawal of reports by victims, lack of facilities, and limited human resources. This study recommends increasing the capacity of law enforcement officers and public education as an effort to strengthen the protection system for victims of Domestic Violence.